Online dictionary learning for Local Coordinate Coding with Locality Coding Adaptors - Pang, Junbiao; Zhang, Chunjie; Qin, Lei; Zhang, Weigang; Qing, Laiyun; Huang, Qingming; Yin, Baocai (Neurocomputing (Amsterdam), 2015)
Dictionary in Local Coordinate Coding (LCC) is important to approximate a non-linear function with linear ones. Optimizing dictionary from predefined coding schemes is a challenge task. This paper focuses on learning dictionary from two Locality Coding Adaptors (LCAs), i.e., locality Gaussian Adaptor (GA) and locality Euclidean Adaptor (EA), for large-scale and high-dimension datasets. Online dictionary learning is formulated as two cycling steps, local coding and dictionary updating. Both stages scale up gracefully to large-scale datasets with millions of data. The experiments on different applications demonstrate that our method leads to a faster dictionary learning than the classical ones or the state-of-the-art methods.